2004
DOI: 10.1007/bf02524346
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of malignant breast tumors in hormone replacement therapy users versus nonusers

Abstract: Breast tumors in HRT users vs. nonusers were of a significantly lower stage and grade and accounted for a higher number of favorable histological types, but all other parameters were similar in the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
6
0
3
Order By: Relevance
“…Several observational studies have reported that breast cancers in hormone users are diagnosed earlier and have histologic and other features that are associated with a better prognosis (Holli et al, 1998;Sacchini et al, 2002;Daling et al, 2003;Pappo et al, 2004) However, results from the Women's Health Initiative (WHI), the only randomised controlled trial of hormone use, showed that hormone users were diagnosed with larger tumours and more likely to have positive lymph nodes (Chlebowski et al, 2003). The study was underpowered to access the effect on grade, histology and hormone receptor status.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies have reported that breast cancers in hormone users are diagnosed earlier and have histologic and other features that are associated with a better prognosis (Holli et al, 1998;Sacchini et al, 2002;Daling et al, 2003;Pappo et al, 2004) However, results from the Women's Health Initiative (WHI), the only randomised controlled trial of hormone use, showed that hormone users were diagnosed with larger tumours and more likely to have positive lymph nodes (Chlebowski et al, 2003). The study was underpowered to access the effect on grade, histology and hormone receptor status.…”
Section: Discussionmentioning
confidence: 99%
“…The lower stage at diagnosis probably reflects also a higher awareness of HRT users for frequent clinical and mammographic screening. Furthermore, women who use HRT tend to belong to the higher socioeconomic classes and have easier access to health facilities (Pappo et al 2004). Despite the less aggressive biological features of ILC, several studies have not found significant differences in disease-free and OS when compared with IDC (Winchester et al 1998, Mersin et al 2003, Arpino et al 2004, Korhonen et al 2004, Molland et al 2004, Ugnat et al 2004, Santiago et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Com a crescente utilização da TH, inúmeros estudos relacionam-na com o aumento na incidência do câncer de mama [3][4][5]7,11 . Entretanto, com a suspensão da terapêutica, o risco para o câncer de mama se reduz, sugerindo que a estrogenioterapia promoveria o crescimento de células tumorais dormentes, tornando o tumor clinicamente detectável mais precocemente 13,18 . No presente estudo, as pacientes com diagnóstico de câncer de mama que usaram TH apresentaram menor faixa etária e menor tempo de menopausa.…”
Section: Discussionunclassified
“…No presente estudo, não foi observada correlação entre o uso de TH e a expressão dos oncogenes c-erbB-2 e p53. A expressão do oncogene c-erbB-2 é encontrada em aproximadamente 25% dos tumores, significando pior prognóstico para as pacientes com câncer de mama 13 . Em 2002, Hur et al 25 constataram que os tumores das pacientes usuárias de TH foram significativamente menores, com menor comprometimento linfonodal e com menor expressão para c-erbB-2, quando comparadas a não usuárias.…”
Section: Variáveisunclassified
See 1 more Smart Citation